2006
DOI: 10.1002/jcp.20569
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate delivers hydrogen peroxide to induce death of ovarian cancer cells and enhances their cisplatin susceptibility

Abstract: The green tea polyphenol epigallocatechin-3-gallate (EGCG) has cancer chemopreventive properties against various types of cancers. The compound is known to attack various targets in transformed cells. In this report, we examined the action of EGCG on ovarian cancer cells. Eight ovarian cancer cell lines were tested (SKOV3, CAOV3, OVCAR3, OVCAR10, A2780, CP70, C30, and C200) and showed IC50s for EGCG at the micromolar range, including ones that are resistant to the chemotherapeutic drug cisplatin. The ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 51 publications
4
87
0
2
Order By: Relevance
“…EGCG increased cisplatin potency by three to six-fold in ovarian cancer cells. They suggest that EGCG may accentuate oxidative stress to inhibit growth of ovarian cancer cells and sensitize them to cisplatin (Chan et al, 2006). In our in vitro study, EC and other green tea extracts do not appear to interfere with the antitumor effect of chemotherapeutic agents (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…EGCG increased cisplatin potency by three to six-fold in ovarian cancer cells. They suggest that EGCG may accentuate oxidative stress to inhibit growth of ovarian cancer cells and sensitize them to cisplatin (Chan et al, 2006). In our in vitro study, EC and other green tea extracts do not appear to interfere with the antitumor effect of chemotherapeutic agents (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…5 Regarding EGCG-induced generation of ROS, hydrogen peroxide production induced by EGCG has been associated with 3-to 6-fold enhancement of cisplatin efficacy in ovarian cancer cells, even in some cell lines highly resistant to the treatment with the drug alone. 24 In leukemia cancer cells, co-treatment with arsenic trioxide (ATO) and EGCG showed oxidative-mediated induction of mitochondrial-dependent apoptosis. 25 EGCG increased intracellular hydrogen peroxide in cancer cells and ATO-induced heme oxygenase-1 (HO-1) provided ferrous iron thus increasing Fenton reaction and, as a consequence, oxidative damage to cells.…”
Section: Redox Modulation Of Anticancer Drugs Effectmentioning
confidence: 99%
“…In addition, Chan et al found that EGCG amplified the toxicity of cisplatin: EGCG increased cisplatin potency by three to 6-fold in ovarian cancer cells [44]. They suggested that EGCG may accentuate oxidative stress to inhibit growth of ovarian cancer cells and sensitize them to cisplatin [45].…”
Section: Discussionmentioning
confidence: 99%